Basis Data Temporal: Aplikasi dan Strategi Impelementasinya - Sutrisno Sutrisno (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Natures of most applications data evolving with time, and previous data state is stillneeded for various things besides current state, such as trend analysis, decision making, andothers. Temporal data is a data inherently with time. Current data will be replaced with anew one. Database temporal is a bitemporal database. A database supports both historicaland transaction database capabilities; it represented with valid-time, and transaction-time.Database temporal can be implemented on relational database model, or object-orienteddatabase model. The low level implementation strategy of database temporal is proposed inthis paper. As consequence, temporal database management system must be built from thescratch. A temporal database engine must be built. Prototype of temporal database engineshave been built both on relational data model, and object-oriented data model.Kata kunci: data temporal, sistem basis data, basis data berorientasi obyek, basis datarelasional, basis data spasio-temporal.